Caring for your baby and young child : birth to age 5 - Altmann, Tanya Remer; Hill, David L; Shelov, Steven P; Hannemann, Robert E (Bantam Books, 2019)
All parents want to provide the very best care for their children. This essential resource from the most respected organization in child health is the one guide pediatricians routinely recommend. Parents can safely trust the guidance, which covers everything from preparing for childbirth to toilet training and from breastfeeding to nurturing your child<U+2019>s self-esteem. Whether it<U+2019>s resolving common childhood health problems or detailed instructions for coping with emergency medical situations, this new and revised edition of Caring for Your Baby and Young Child has everything you need, with information on . . . <U+2022> Basic care from infancy through age five <U+2022> Milestones for physical, emotional, social, and cognitive growth, as well as visual, hearing, language, and movement mileposts <U+2022> Information on healthy development and disabilities, including what to watch for and when to seek help <U+2022> Injuries, illnesses, congenital diseases, and other disabilities addressed in a complete health encyclopedia <U+2022> Updated content dedicated to environmental hazards and allergies <U+2022> Guidelines for prenatal and newborn care, with spotlights on maternal nutrition, exercise, and screening tests during pregnancy <U+2022> An in-depth discussion of breastfeeding, including its benefits, techniques, and challenges <U+2022> Revised nutrition recommendations, including the importance of early introduction of allergenic foods and obesity prevention tips <U+2022> Updated safety standards: the very latest AAP recommendations, from CPR instruction, safe sleep, and immunizations to childproofing tips, car safety seats, and toy safety <U+2022> Tips for choosing childcare programs <U+2022> Cutting edge research on early brain development and how babies and young children think <U+2022> Updated media chapter, including the effects of media and technology exposure on children and how to make the most of screen time in the home